Assessing deforestation leakage associated with the scaling of sustainable land use systems to inform land use policy in Colombia - Aja, Daniel; Sylvester, Janelle; Gutierrez Zapata, Diana; Castro Nunez, Augusto (2024)
Colombia's commitment to scaling sustainable land use systems (SLUS) as part of its Nationally Determined Contributions alongside its pledge to achieve zero net deforestation by 2030 presents a critical challenge: how to ensure that the widespread adoption of these systems does not inadvertently lead to increased deforestation in surrounding landscapes. While the benefits of SLUS at the farm scale are well-documented, their implications for land-use/cover changes (LUCC) in broader landscapes remain poorly understood. This research aims to address this knowledge gap by comprehensively analyzing deforestation dynamics associated with the adoption of SLUS, specifically silvopasture and cacao agroforestry systems, in Caquetá, Colombia. We employed a rigorous proximity and counterfactual analysis, using georeferenced field data on SLUS implementation and the Global Forest Watch tree cover loss dataset, to examine the pattern of deforestation from 2001 to 2023. We utilized a multi-criteria decision-making framework, including the analytical hierarchy process, to pinpoint similar areas where SLUS were not implemented that served as control points. Our results showed that CP3 and CP2 experienced the highest rates of tree cover loss (4.5% and 2.4%), while the Buffer and SLUS areas had the lowest (0.9% and 1.2%). In 2022, the tree cover loss in CP3, CP2, SLUS, and Buffer were 1.8%, 1.3%, 0.6% and 0.4%. We observed strong correlations between tree cover loss in SLUS and Buffer (r = 0.96) and CP2 and CP3 (r = 0.86) suggesting interconnected deforestation dynamics. The ARIMA model predicts continued stabilization of tree cover loss in SLUS and Buffer areas from 2023 to 2027. Preliminary results indicate no evidence of leakage. However, this result will be compared with country specific datasets such as data produced by SINCHI and IDEAM to confirm this finding.